Wycena instrumentów finansowych w banku w aspekcie FVO - Niewiadoma, Maria (Valuation of the Financial Instruments in Banks in the Aspect of FVO, 2007)
The role of financial instruments in the financial sector has been still risen during the process of globalization of the financial market. IAS 32 has information about different classification of financial instruments, for example: trade accounts receivable and payable, notes receivable and payable, loans receivable and payable and bonds receivable and payable. IAS 39 and IFRS 7 and Polish accounting law inform about the possibility to use in banks four financial instruments: fair value option (FVO) connect with profit and loss account, amortization cost, market price or net selling price in different situations.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1158, s. 253-260